Optimization of RF signal detection and alert system for restricted area - Ili Najaa Aimi Mohd Nordin; Najla Aiman Nazari; Muhammad Rusydi Muhammad Razif; Nurulaqilla Khamis; Noraishikin Zulkarnain; Farkhana Muchtar; Nor Aira Zambri (Institute of Advanced Engineering and Science, 2019)
This paper presents study on optimizing RF signal detection and alert system for restricted area. Nowadays, mobile phone utilization is very common among youngsters. Despite of being very useful for educational purpose, it turns into a noteworthy issue while being smuggled into restricted area, such as examination hall and used as a cheating tool. To overcome this problem, an advancement on the detection and alert system of active mobile phone was proposed by implementing RF signal detection system optimization using multi-band dipole antenna and alert system utilizing LED and camera. The system demonstrated higher sensitivity to 3G signal followed by GSM and Wi-Fi with the decrease in voltage value across the LED when distinguishing 3G, GSM and Wi-Fi signal with the estimation of 2.316 V, 1.162 V and 1.054 V respectively. The alert system was improved by activating LED and camera instead of buzzer in displaying the region of the active mobile phone. The camera was able to effectively capture the conceivable cheating area when active mobile phone is present. The images of the potential cheating region can be recovered from the computer. This framework can assist the invigilators with being cautioned to the potential regions of cheating using mobile phone.